2012
DOI: 10.1590/s1413-70542012000300012
|View full text |Cite
|
Sign up to set email alerts
|

Yeast as a feed additive for training horses

Abstract: This research analyses the yeast supplementation effect on the digestibility of nutrients and metabolic performance in training horses. Twelve horses were assigned into 2 groups: Pr (20 g of probiotics daily per horse) and control. The diet consisted of roughage (haylage) and commercial rations and all horses were trained for 6 weeks. LIPE ® indicator was used during 7 days and feces collected for five days to determine nutrient digestibility. DM, CP, DE, P, NDF, ADF, HCEL and lignin were determined. All horse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…However, differences (P<0.05) were found between the maximal-effort physical tests for time-to-fatigue, aerobic and anaerobic thresholds, SLa 2 , SLa 4 , and S 200 (Table 1). Rezende et al (2012) did not observe effects of daily supplementation with 20 g probiotics on physical performance of Andalusian horses subjected to six weeks of training.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…However, differences (P<0.05) were found between the maximal-effort physical tests for time-to-fatigue, aerobic and anaerobic thresholds, SLa 2 , SLa 4 , and S 200 (Table 1). Rezende et al (2012) did not observe effects of daily supplementation with 20 g probiotics on physical performance of Andalusian horses subjected to six weeks of training.…”
Section: Resultsmentioning
confidence: 57%
“…According to Rezende et al (2012), different responses observed in studies using probiotics in horses may be due to differences in the amount of live yeast supplement given to the animals, as there are no studies suggesting the ideal dose to be used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden shift in diets or highly fermentable sugar or starch rich diets disturb the microbial balance due to low digestibility of plant cell wall carbohydrates by the horses as compared to the ruminants. In horses the digestive system has a comparatively faster rate of passage leaving the microflora of the large intestine with less time to carry out fermentation, and this leads to accumulation of lactate and reduction in pH leading to subclinical acidosis in the caecum-colon, consequently increasing the horses' susceptibility to colic pain or laminitis (Kronfeld and Harris, 1997;Hudson et al, 2001;Respondek et al, 2007;Jouany et al, 2008;de Rezende et al, 2012). Therefore, it is important to overcome these intestinal disorders to maintain healthy gut flora.…”
Section: Probiotic Yeasts and Horsesmentioning
confidence: 99%
“…Therefore, it is important to overcome these intestinal disorders to maintain healthy gut flora. Many strategies have been adopted for this purpose and one such strategy is the addition of probiotic yeast or live yeast in horses' diet to improve diet assimilation and to encourage horses' growth and performance (Julliand et al, 2006;Moura et al, 2009;Moura, 2011;de Rezende et al, 2012). According to Chaucheyras-Durand and Durand (2010) probiotic supplementation needs to fulfill certain targets in the horse to be beneficial such as, to limit stress and improve hindgut fermentation, milk quality and quantity.…”
Section: Probiotic Yeasts and Horsesmentioning
confidence: 99%